New-onset psychosis following COVID-19 vaccination: a systematic review - Lazareva, Marija; Renemane, Lubova; Vrublevska, Jelena; Rancans, Elmars (Frontiers in Psychiatry, 2024)
Background The emergence of a new coronavirus strain caused the COVID-19 pandemic. While vaccines effectively control the infection, it’s important to acknowledge the potential for side effects, including rare cases like psychosis, which may increase with the rising number of vaccinations. Objectives Our systematic review aimed to examine cases of new-onset psychosis following COVID-19 vaccination. Methods We conducted a systematic review of case reports and case series on new-onset psychosis following COVID-19 vaccination from December 1st, 2019, to November 21st, 2023, using PubMed, MEDLINE, ClinicalKey, and ScienceDirect. Data extraction covered study and participant characteristics, comorbidities, COVID-19 vaccine details, and clinical features. The Joanna Briggs Institute quality assessment tools were employed for included studies, revealing no significant publication bias. Results A total of 21 articles described 24 cases of new-onset psychotic symptoms following COVID-19 vaccination. Of these cases, 54.2% were female, with a mean age of 33.71 ± 12.02 years. Psychiatric events were potentially induced by the mRNA BNT162b2 vaccine in 33.3% of cases, and psychotic symptoms appeared in 25% following the viral vector ChAdOx1 nCoV-19 vaccine. The mean onset time was 5.75 ± 8.14 days, mostly reported after the first or second dose. The duration of psychotic symptoms ranged between 1 and 2 months with a mean of 52.48 ± 60.07 days. Blood test abnormalities were noted in 50% of cases, mainly mild to moderate leukocytosis and elevated C-reactive protein. Magnetic resonance imaging results were abnormal in 20.8%, often showing fluid-attenuated inversion recovery hyperintensity in the white matter. Treatment included atypical antipsychotics in 83.3% of cases, typical antipsychotics in 37.5%, benzodiazepines in 50%, 20.8% received steroids, and 25% were prescribed antiepileptic medications. Overall, 50% of patients achieved full recovery. Conclusion Studies on psychiatric side effects post-COVID-19 vaccination are limited, and making conclusions on vaccine advantages or disadvantages is challenging. Vaccination is generally safe, but data suggest a potential link between young age, mRNA, and viral vector vaccines with new-onset psychosis within 7 days post-vaccination. Collecting data on vaccine-related psychiatric effects is crucial for prevention, and an algorithm for monitoring and treating mental health reactions post-vaccination is necessary for comprehensive management. Systematic review registration https://www.crd.york.ac.uk/PROSPERO, identifier CRD42023446270.